The Influence of Digital Marketing, Brand Awareness, and Sales Promotion on the Purchase Decision of Lenovo Laptop at PT. Dayamega Pratama - Martin, Ricky; Fitriano, Andre; Novia, Dessy; Boni, Noviyanti; Surniati, Surniati (Budapest International Research and Critics University, 2021)
This study aims to examine and analyze the influence of digital marketing, brand awareness and sales promotion on purchasing decisions for Lenovo Laptops at PT Dayamega Pratama. The phenomenon studied in this study includes digital marketing because many companies currently rely on sales using digital marketing. And what is interesting in the sales promotion of a product in the absence of promotion can be sold and how much influence sales promotion has on purchasing decisions. Simple random sampling was used as a sampling method. The sample used as many as 151 people. The data analysis method used multiple linear regression. In partial data testing, digital marketing has a positive and significant effect on purchasing decisions, brand awareness has a positive and significant effect on purchasing decisions, and sales promotion has a positive and significant effect on purchasing decisions on purchasing decisions for Lenovo Laptops at PT Dayamega Pratama. In the simultaneous data analysis test, the digital marketing, brand awareness and sales promotion variables showed a positive and significant influence on the purchasing decision of Lenovo Laptops at PT Dayamega Pratama.